Construction of Ms6 derivative mutants as tools for interaction studies ith mycobacteria - Pombo, Sofia Pires de Oliveira (2015)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2015